IDDF2019-ABS-0342 Evaluation of bowel cancer awareness among undergraduate pharmacy students in malaysia and pakistan: a cross-sectional study. (7th June 2019) - Ahmad, Sohail; Ali, Rooha; Qamar, Muhammad; Shaikh, Faiz Ahmed; Khan, Nauman Rahim; Selvaraj, Amutha
Abstract : Background: As a pharmacist-wannabes, the final year undergraduate pharmacy students must have adequate foundational cancer knowledge and training to educate the public regarding the identification of warning signs and risk factors of bowel cancer. This study was conducted to assess and compare the levels of bowel cancer awareness among pharmacy students in Malaysia and Pakistan. Methods: In this multi-centre cross-sectional study, a total of 174 final year undergraduate pharmacy students were enrolled from two Malaysian and two Pakistani universities. Post-approval from Cancer Research UK, a pre-validated Bowel Cancer Awareness Measure (CAM) was used. Bowel CAM consists of eight questions with a total of 26 items focusing on warning signs (10 items), delay in seeking medical help (1 item), bowel age (1 item), risk factors (11 items), bowel cancer screening programme (2 items), knowledge (1 item), age of first invitation (1 item), and confidence in detecting bowel symptom (1 item). The extracted data from the completed questionnaires were analysed descriptively and inferentially using the Statistical Package for the Social Sciences (SPSS (R) ), version 22. Results: The mean age of enrolled students was 22.78, SD=1.77, and the majority of them were females (n=107, 61.5%), and Malaysians (n=111, 63.8%). The enrolled students possessed high and moderate levels of awareness regarding bowel cancer warning signs (n=129, 74.1%), and risk factors (n=148, 85.1%), respectively. The findings of an independent-samples t-test suggested that there was a statistically significant difference in warning signs awareness score in Malaysian (M=24.13, SD=2.67), and Pakistani students [M=22.57, SD=3.43; t(172)=3.332, p=0.001]; whereas, this difference was insignificant for the scores of risk factors (M=32.59, SD=4.20), [M=31.30, SD=4.65; t(172)=1.875, p=0.062]. Moreover, a significant positive correlation was found between scores of warning signs and risk factors (r=0.364, p=0.001). Conclusions: Malaysian students showed a better score for Bowel CAM. Specialised periodic training sessions can be helpful to enhance awareness among these future pharmacists.